Nintendo case: evolution or involution in the protection of community design? Comment on the judgment of September 27, 2017, joined cases C-24/16 and C-25/16 - Jiménez Serranía, Vanessa (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
The Judgment of the CJEU of September 27th, 2017, better known as the “Nintendo case” represents an important jurisprudential milestone in the field of community design protection. The CJEU, in this Judgment, addresses certain key aspects related to the practical application, at the procedural level, of the protection granted by the Community design. In particular, it examines the case in which there is a plurality of offenders located in different Member States who market products for several countries via Internet. Secondly, in this judgment the CJEU determines, in a questionable manner, the contours to an “almost” unknown restriction of the rights granted to the holder of a community design: the “citation” limitation.